Rare plant species of salt marshes of the Croatian coast - Dítě, Daniel; Dítětová, Zuzana; Eliáš jun., Pavol; Šuvada, Róbert (Hacquetia, 2018)
Between 2011 and 2016 we surveyed 42 sites of coastal salt marshes of Croatia. We confirmed the occurrence of several rare and endangered plant species. Ten of them are included in the Red List of Croatia; critically endangered (CR) Eleocharis uniglumis, Triglochin barrelieri and T. maritima, endangered (EN) Carex divisa and C. extensa, vulnerable (VU) Parapholis incurva, Salsola soda and Suaeda maritima and category data deficient (DD) Limonium virgatum and Puccinellia festuciformis. We also report localities of other rare taxa of salt marshes like Allium telmatum, Tripolium pannonicum subsp. tripolium, Juncus gerardii, Parapholis filiformis, Plantago cornuti, Samolus valerandi and Scorzonera parviflora. Several plant species are endangered. Their habitats, salt marshes were converted into fields or destructed by construction for developing tourist infrastructure. Today only a part of the remained areas are under protection.